2018
DOI: 10.3389/fendo.2018.00358
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Secondary to Acromegaly: Physiopathology, Clinical Features and Effects of Treatment

Abstract: Acromegaly is a rare disease due to chronic GH excess and to the consequent increase in IGF-1 levels. Both GH and IGF-1 play a role in intermediate metabolism affecting glucose homeostasis. Indeed, chronic GH excess impairs insulin sensitivity, increases gluconeogenesis, reduces the glucose uptake in adipose tissue and muscle and alters pancreatic β cells function. As a consequence, glucose metabolism alterations are a very frequent complication in acromegaly patients, further contributing to the increased car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
0
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 106 publications
(125 reference statements)
0
89
0
7
Order By: Relevance
“…One of these, Pegvisomant, has completed a phase II clinical trial for modulating insulin sensitivity in subjects with pre-diabetes (NCT02023918). Pegvisomant is used to treat acromegaly by blocking the binding of endogenous growth hormone to growth hormone receptor (GHR) [33][34][35] , and has been shown to improve insulin sensitivity in acromegaly patients 36,37 . The association between the T2D PRS and GHR levels was consistent with repurposing, suggesting Pegvisomant may reduce T2D risk by inhibiting GHR function.…”
Section: Resultsmentioning
confidence: 99%
“…One of these, Pegvisomant, has completed a phase II clinical trial for modulating insulin sensitivity in subjects with pre-diabetes (NCT02023918). Pegvisomant is used to treat acromegaly by blocking the binding of endogenous growth hormone to growth hormone receptor (GHR) [33][34][35] , and has been shown to improve insulin sensitivity in acromegaly patients 36,37 . The association between the T2D PRS and GHR levels was consistent with repurposing, suggesting Pegvisomant may reduce T2D risk by inhibiting GHR function.…”
Section: Resultsmentioning
confidence: 99%
“…Hyperglycemia can occur in MAS with the development of GH excess and/or hypercortisolemia . However, a specific association between MAS and hyperglycemia due to DM has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…2 Hyperglycemia can occur in MAS with the development of GH excess and/or hypercortisolemia. 9,10 However, a specific association between MAS and hyperglycemia due to DM has not been established. Sung et al described a 23-year-old male with MAS and recently diagnosed DM treated with an oral antidiabetic medication only.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, IGF-1 improves peripheral insulin sensitivity but is not enough to override the diabetogenic action of chronic GH excess. 5 Studies have demonstrated the association of IGF-1 levels and DM as predictors of mortality in acromegaly. 6,7 Adrenocorticotrophic hormone hypersecretion Cushing's disease, or ACTH-secreting pituitary adenoma, is another recognised cause of DM.…”
Section: European Endocrinologymentioning
confidence: 99%